BCG vaccination impact on mortality and recovery rates in COVID-19: A meta-analysis - Surjit Singh; Daisy Khera; Ankita Chugh; Sameer Khasbage; Pushpinder S. Khera; Vinay Kumar Chugh (Monaldi Archives for Chest Disease, 2021)
COVID-19 is a pandemic caused by SARS-CoV-2 virus which is a very worrisome public health emergency. In this study, we compared the mortality rate and recovery rate in countries with and without BCG vaccination policy. The data of mortality of COVID-19 was extracted from worldometer (https://www.worldometers.info/coronavirus/) on 26th July 2020. The data of countries where BCG vaccination is being done for all individuals is taken from BCG world atlas (http://www.bcgatlas.org/index.php), updated in 2017. BCG vaccination policy recommended countries are intervention group versus countries without BCG vaccination policies which are regarded as control group. Pooled analysis of countries with and without BCG vaccination policy revealed mortality rate of 1.31% (95%CI – 1.31% to 1.32%; I2 = 100%, p<0.01) and 3.25% (95%CI – 3.23% to 3.26%; I2 = 100%, p<0.01), respectively. The recovery rate in two country groups were found to be 72.60% (95%CI – 72.57% to 72.63%) and 55.94% (95%CI – 55.90% to 55.98%), respectively. 52 individuals need to be BCG vaccinated to prevent one death (NNT = 52). In BCG vaccination program countries, there is statistically and clinically significant less mortality (p-value <0.001) as compared to countries without BCG policy. Our findings corroborate the hypothesis that BCG vaccination may provide protection from COVID-19. High quality evidence from randomised controlled trials are required to establish causality between BCG vaccination and protection from severe COVID-19.